2007
DOI: 10.1071/ea06130
|View full text |Cite
|
Sign up to set email alerts
|

Short term fasting as a tool to design effective grazing strategies for lactating dairy cattle: a review

Abstract: Varying the time since the last meal (i.e. fasting) is a means of manipulating foraging behaviour. Management practices that restrict grazing time, and/or change the timing of the grazing session, may be analogous to changes introduced with different fasting regimes, suggesting that the same pattern of responses on foraging behaviour could be expected. Concepts related to eating patterns of grazing dairy cows are briefly reviewed, and impacts of short-term (i.e. within day) fasts on ingestive behaviours are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 27 publications
7
54
0
9
Order By: Relevance
“…The opposite occurred for PRE cows. These findings support the idea that after a period of fasting, rumination can be postponed in favor of grazing (Kennedy et al, 2009) and that rumination bouts tend to occur 1 to 2 h after the start of grazing (Chilibroste et al, 2007;Gregorini et al, 2012). Furthermore, rumination in sheep was not found to be a synchronized activity (Rook and Penning, 1991), which could suggest that animals can decide to engage in rumination on an individual basis.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The opposite occurred for PRE cows. These findings support the idea that after a period of fasting, rumination can be postponed in favor of grazing (Kennedy et al, 2009) and that rumination bouts tend to occur 1 to 2 h after the start of grazing (Chilibroste et al, 2007;Gregorini et al, 2012). Furthermore, rumination in sheep was not found to be a synchronized activity (Rook and Penning, 1991), which could suggest that animals can decide to engage in rumination on an individual basis.…”
Section: Discussionsupporting
confidence: 79%
“…Research conducted by Gregorini et al (2009) andChilibroste et al (2007) described the potential use of a fasting period in dairy cows, as a means to increase subsequent grazing behavior. The latter author suggested the possibility of using time since last meal as a means of inducing feeding motivation, which could be the case of PRE cows in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions of the simulations are described in Table 3. or manure management. In practice, daily access time at pasture could also be used as a grazing management tool if a time constraint would allow increasing grazing efficiency through manipulation of foraging behaviour (Chilibroste et al, 2007). If short-term behavioural adaptation following feed deprivation is well known (Chilibroste et al, 2007), the extent to which time availability affects dairy cow performance and intake, as well as behavioural adaptation mechanisms have been recently studied in various situations at daily scale.…”
Section: Variation Of Nutrient Supply At Grazing Relative To Animal Rmentioning
confidence: 99%
“…In practice, daily access time at pasture could also be used as a grazing management tool if a time constraint would allow increasing grazing efficiency through manipulation of foraging behaviour (Chilibroste et al, 2007). If short-term behavioural adaptation following feed deprivation is well known (Chilibroste et al, 2007), the extent to which time availability affects dairy cow performance and intake, as well as behavioural adaptation mechanisms have been recently studied in various situations at daily scale. In recent studies, it has been reported that, with lowto-medium supplementation levels, MY is generally reduced when daily time at pasture, given in one grazing session daily, is ,8 h (Kristensen et al, 2007;Delaby et al, 2008).…”
Section: Variation Of Nutrient Supply At Grazing Relative To Animal Rmentioning
confidence: 99%